Investigation of phonological and lexical balance in Anvari's sonnets - Vahid Alibaygi sarhali; Omolbanin Nikkhahe Noori (مطالعات زبانی و بلاغی)
The music of poetry is one of the most beautiful and appealing elements of poetic texts, which is found in Anvari's sonnets, which is accompanied by repetition and balance. Anvari, with the help of phonetic balance, and the use of a slight balance, used many different metaphors in his poetry, which increased the rhythm of his sonnets. He balances the types of repetitions with a slight balance so that repetitive consonants and vowels with a high frequency of consonants "D", "R" and enjoyment of the long vowel "A" are the lyrics. In the discussion of lexical balance, Anvari uses a variety of repetitions of a complete linguistic form, which is well known by repeating the types of nouns, verbs, and words in the beginning, between and in the rhyme position, so that repetition of the verb in the rhyme position is more frequent. He uses the complete repetition of a linguistic form in the form of menadas and sentences, and by using; a repetition of an incomplete linguistic form makes it possible to use a variety of puns in the sonnet, which is more pronounced with repetition of puns and lines. . Thus, it can be said that Anvari has given certain music to his sonnets using a variety of consonants and repeating a complete and incomplete linguistic form. We have identified in Anvari's sonnets, and then analyzed each of them, specifying the frequency of each in the form of graphs.